Bank Lending and the European Sovereign Debt Crisis - De Marco, Filippo (Journal of Financial and Quantitative Analysis, 2019)
I investigate whether bank exposures to sovereign debt during the European debt crisis affected the real economy. I show that a shock to the marked-to-market (MTM) value of bank exposures to sovereign debt led to credit tightening in 2010–2011 that had negative real effects on small and young firms. Because banks do not usually mark their holdings of sovereign bonds to market, I explore the transmission channels of the unrealized losses on credit supply. I show that a shock to MTM exposures reduced short-term bank funding from U.S. money market funds rather than affecting equity or working through alternative channels.